Training Addiction Counselors to Deliver A Brief Psychoeducational Intervention for Chronic Pain among Patients in Opioid Agonist Treatment: A Pilot Investigation. Issue 2 (April 2018) - Butner, Jenna L.; Bone, Curtis; Ponce Martinez, Caridad C.; Kwon, Grace; Beitel, Mark; Madden, Lynn M.; Bono, Madeline H.; Eller, Anthony; Barry, Declan T.
Background: Despite high rates of chronic pain among their patients, opioid agonist treatment (OAT) counselors report an absence of training to manage chronic pain. Methods: A multidisciplinary team developed a tailored training for counselors to screen and address chronic pain via a brief psychosocial intervention, and implemented it with 52 addiction counselors. Data on knowledge (9 true-false items) as well as attitudes, interest, and perceived ability (scored on 5-point Likert-type scales) were collected from counselors before (pre-test), after (post-test) training, and after 6 months (follow-up). Results: Pre-test knowledge scores varied considerably. Compared to pre-test, mean counselor knowledge scores increased significantly post-training and at follow-up (p's.<05). The training was associated with increases in positive attitudes toward the role of counselors in managing chronic pain, interest in assessing chronic pain, and counselor ability to assess as well as suggest appropriate interventions for pain (all p's <.05). Perceived ability to assess chronic pain and suggest appropriate treatment interventions were higher at follow-up than at pre-test (p's <.05). Conclusions: Findings related to the initial evaluation of this training were promising, and future research is warranted to further examine the efficacy of training drug counselors on psychosocial interventions to manage chronic pain among OAT patients.